Latar Belakang Peran Aktif Jepang di Anti-Piracy Asia Tenggara dalam Perspektif Konstruktivisme - Swastika, Mayora Bunga (Universitas Muhammadiyah Yogyakarta, 2017)
This article explains the identity of Japan that influences Japan's active role in Southeast Asia anti-piracy. Japan has been making efforts to fight against piracy in the Southeast Asia waters, such as dialogue partnerships, capacity building, and joint exercises with Southeast Asian countries. Japan also initiated the establishment of the Regional Cooperation Agreement to Combat Hijacking and Armed Robbery against Ships (ReCAAP). This evokes a question, why does Japan as an East Asia country join and make efforts to combat piracy in Southeast Asia? The purpose of this article is to understand the reasons behind state efforts about an issue in other regions. Identity theory used in this article to analyze the reasons for Japan’s active role in Southeast Asia anti-piracy. This article uses literature study by collecting related data, such as Japan’s role in Southeast Asia anti-piracy. This article shows that Japan's identity as a maritime country is influencing Japan’s behavior to participate actively in Southeast Asia anti-piracy cooperation. Artikel ini menjelaskan tentang identitas Jepang yang mempengaruhi peran aktif Jepang dalam upaya anti-piracy di wilayah Asia Tenggara. Jepang telah melakukan upaya untuk menangani perompakan yang terjadi di wilayah laut Asia Tenggara. Upaya yang dilakukan Jepang seperti dialog-dialog, capacity building, latihan bersama dengan negara-negara Asia Tenggara. Jepang juga menginisiasi pembentukan Regional Cooperation Agreement on Combating Piracy and Armed Robbery against Ships (ReCAAP). Hal ini menimbulkan pertanyaan, mengapa Jepang sebagai negara di Asia Timur ikut menangani perompakan di wilayah Asia Tenggara? Tujuan dari artikel ini adalah untuk memahami alasan negara melakukan upaya-upaya menangani suatu isu di kawasan lain dan memahami kepentingan negara dalam suatu kerja sama. Teori identitas digunakan untuk menganalisis alasan Jepang berperan aktif menangani perompakan di Asia Tenggara. Artikel ini menggunakan studi pustaka dengan mengumpulkan data-data yang terkait dengan peran yang telah dilakukan oleh Jepang di kawasan Asia Tenggara untuk menangani perompakan. Pada akhirnya, artikel ini menunjukkan bahwa identitas Jepang sebagai negara maritim mempengaruhi perilaku Jepang ikut berperan aktif dalam menangani perompakan di wilayah Asia Tenggara.